A novel experimental set-up for in-situ microstructural characterization during continuous strain path change. Issue 1 (November 2020) - Dhara, S; Taylor, S; Figiel, Ł; Shollock, B; Hazra, S
Abstract: Strain path change is a typical phenomenon during continuous stamping operations of sheet metal for a variety of applications including automotive body parts. During stamping, a punch continuously deforms a metal sheet to produce a desired geometry while following various strain path transitions depending on overall design of the stamping process. The strain path change can potentially alter the expected forming limit of the material. Previous researchers investigated the effect of changing strain path by loading sample in two distinct steps. Typically, between the steps the sample is unloaded before being re-loaded in the new strain path. This practice reflects the key challenge in elucidating this strain path dependent deformation, which is the ability to control the strain path change in a single deformation stage in an experimental set-up. In this work, a novel testing rig and specimen geometry that is capable of changing the strain path of a sample continuously without unloading the specimen were conceptualised, modelled and subsequently manufactured. Using this apparatus, the specimen was deformed in the uniaxial strain path in the first step before being deformed biaxially without unloading in between the steps. Thus, the apparatus ensures that the sample undergoes a continuous strain path change without unloading between the steps. The size of this mechanical test rig permits it to be placed inside a scanning electron microscope (SEM) chamber in order to study strain path transition in-situ to highlight strain localization and related microstructural changes in real time. Utilizing this test set-up, strain path change and corresponding strain values along each strain path were evaluated. The changes in material microstructure were concurrently investigated using in-situ SEM and electron back scattered diffraction (EBSD) analysis.